The Occurrence of Richter's Syndrome during Treatment with Obinutuzumab and Chlorambucil. (16th July 2020) - Ng, Teng Fong; Carnley, Benedict; Green, Celia; Spagnolo, Dominic; Leahy, Michael F.
Abstract : Chronic lymphocytic leukaemia is a slow-growing leukaemia of developing B-lymphocytes, which may transform to an aggressive lymphoma known as Richter's syndrome. While Richter's syndrome can present in untreated or relapsed-refractory cases, it may occur upon the commencement of less intensity treatment regimens. We present a case of Richter's syndrome following treatment with chlorambucil and obinutuzumab and review of available literature on the topic.